A wireless ECG monitoring system for pervasive healthcare. (1st December 2006) - Sneha, Sweta; Varshney, Upkar
This paper presents an architectural framework of a system utilising mobile technologies to enable continuous, wireless, electrocardiogram (ECG) monitoring of cardiac patients. The proposed system has the potential to improve patients' quality of life by allowing them to move around freely while undergoing continuous heart monitoring and to reduce healthcare costs associated with prolonged hospitalisation, treatment and monitoring.